A cluster‐randomised, controlled trial of the impact of Cogmed Working Memory Training on both academic performance and regulation of social, emotional and behavioural challenges. (8th October 2016) - Hitchcock, Caitlin; Westwell, Martin S.
Abstract : Background: We explored whether school‐based Cogmed Working Memory Training (CWMT) may optimise both academic and psychological outcomes at school. Training of executive control skills may form a novel approach to enhancing processes that predict academic achievement, such as task‐related attention, and thereby academic performance, but also has the potential to improve the regulation of emotion, social problems and behavioural difficulties. Methods: Primary school children (Mean age = 12 years, N  = 148) were cluster‐randomised to complete active CWMT, a nonadaptive/placebo version of CWMT, or no training. Results: No evidence was found for training effects on task‐related attention when performing academic tasks, or performance on reading comprehension and mathematics tasks, or teacher‐reported social, emotional and behavioural difficulties. Conclusions: CWMT did not improve control of attention in the classroom, or regulation of social, emotional and behavioural difficulties.